Hypoglycemia due to insulin autoimmune syndrome (Hirata’s disease): a rare cause of hypoglycaemia - Patel, Het V.; Kumar, Sunil; Moradiya, Kalpesh; Shah, Vidhi (International Journal of Advances in Medicine, 2021)
Although the most common cause of recurrent hypoglycaemia is diabetes mellitus as patient is on antidiabetic medications which can be prevented by modification of antidiabetic doses, nutrition therapy and lifestyle modifications. Some endogenous hyperinsulinemic conditions like insulinoma, functional beta cell disorders and insulin autoimmune syndromes, hormonal deficiencies can cause serious and sometimes life threatening hypoglycaemia. So further laboratory evaluation like plasma/serum glucose levels, c-peptide levels, insulin levels, insulin antibodies and imaging studies are needed to evaluate unexplained hypoglycaemia. Here we report a case of insulin autoimmune syndrome in a 67 year old Indian male who had presented to us with multiple episodes of spontaneous hypoglycaemia. On further workup, the patient was found to have endogenous hyperinsulinemic hypoglycemia. As the patient’s abdominal imaging revealed no apparent cause of EHH, on further evaluation he came positive for insulin antibodies. Patient was diagnosed as IAS and he was given frequent small meals and complex carbohydrate diet and he had improved symptomatically. The incidence of IAS is most common in Japan and very few cases have been reported from India, so it should be kept in differential diagnosis of recurrent hypoglycaemia.